Brief Report: Endothelial‐Specific X‐Box Binding Protein 1 Deficiency Limits Tumor Necrosis Factor–Induced Leukocyte Recruitment and Vasculitis. Issue 12 (25th November 2015) - Ziogas, Athanasios; Muders, Michael H.; Economopoulou, Matina; Sprott, David; Grossklaus, Sylvia; Siegert, Gabriele; Baretton, Gustavo B.; Mitroulis, Ioannis; Chavakis, Triantafyllos
Abstract : Objective: Endothelial cell activation by tumor necrosis factor (TNF) and associated leukocyte infiltration are hallmarks of vasculitis. The aim of this study was to investigate the potential role of the cellular stress–associated endothelial X‐box binding protein 1 (XBP‐1) transcription factor in TNF‐induced endothelial cell inflammation and vasculitis. Methods: Mice with an endothelial cell–specific XBP‐1 deficiency were used in a modified local Shwartzman reaction (LSR) model of TNF‐induced small vessel vasculitis. To address the contribution of XBP‐1 to the TNF‐mediated inflammatory response in endothelial cells, we examined the activation of XBP‐1 expression by TNF as well as the effect of XBP‐1 knockdown in endothelial cells on TNF‐induced signaling, proinflammatory gene expression, and leukocyte–endothelial cell adhesion. Results: The active spliced form of XBP‐1 in endothelial cells was triggered by TNF. In addition, endothelial XBP‐1 contributed to the sustained TNF‐triggered NF‐κB−dependent transcriptional activation of proinflammatory molecules, which was associated with leukocyte–endothelial cell adhesion. In the LSR model, endothelial cell–specific XBP‐1–deficient mice displayed significantly less vascular damage, accompanied by reduced perivascular neutrophil infiltration, as compared with wild‐type mice. Conclusion: Endothelial XBP‐1 is activated by TNF and regulates leukocyte–endothelial cell adhesion in vitro as well as neutrophil infiltration and vascular damage in murine vasculitis.